2011
DOI: 10.1016/j.limno.2010.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reduced salt concentrations on plant communities in the River Werra (Germany)

Abstract: a b s t r a c tThe reduction and equalization of the salt concentrations in the River Werra have resulted in a gradual recovery of the aquatic flora. Spatial high-resolution macrophyte mappings document the spread of the aquatic vascular plants in the middle and lower River Werra. Simultaneously, the plankton blooms have declined. Changes in the composition of the algal communities including diatoms also indicated lower salinity. In addition to the salinity, high nutrient concentrations, waste water discharges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 2 publications
(2 reference statements)
0
11
0
Order By: Relevance
“…Evans et al (2014) demonstrated temporal decay of geologic influence on individual mine discharges, a finding that influenced our approach here. Bäthe and Coring (2011) and Coring and Bäthe (2011) reported declining mining-origin salinity over a 17-year period in Germany's River Table 4 Dissolved trace metals and other trace elements in the Powell River, 2000-2011, as concentrations and relative to CCC (estimated at 100 mg/L hardness); with statistically significant results of linear model testing for spatial (vs. river km) and temporal (vs. time) effects on the elements. (1-3.59) 1.4 (0.8-3.0) ns ns a pos = positive; neg = negative; ns = not significant (p b 0.05).…”
Section: Water Qualitymentioning
confidence: 99%
“…Evans et al (2014) demonstrated temporal decay of geologic influence on individual mine discharges, a finding that influenced our approach here. Bäthe and Coring (2011) and Coring and Bäthe (2011) reported declining mining-origin salinity over a 17-year period in Germany's River Table 4 Dissolved trace metals and other trace elements in the Powell River, 2000-2011, as concentrations and relative to CCC (estimated at 100 mg/L hardness); with statistically significant results of linear model testing for spatial (vs. river km) and temporal (vs. time) effects on the elements. (1-3.59) 1.4 (0.8-3.0) ns ns a pos = positive; neg = negative; ns = not significant (p b 0.05).…”
Section: Water Qualitymentioning
confidence: 99%
“…For example at the Gerstungen monitoring site Nitrogen concentrations varied between 1.35 and 20.7 mg/l, the total phosphorus concentrations were 0.12-0.85 mg/l in the time period from 2005 to 2007 (Dietrich and Schumann 2006;Thüringer Landesanstalt für Umwelt und Geologie 2007;Bäthe 2009). The River Werra exhibits a phytal biomass production that is many times greater than in other rivers of similar size (DVWK 1998;Bäthe 2009;Coring and Bäthe this volume). The autotrophic biomass production has increasingly affected water quality in the rivers Werra and Weser with so-called secondary pollution.…”
Section: Dissolved Nutrientsmentioning
confidence: 99%
“…The lack of monitoring and management standards is problematic because even if the sources of salinization were to be eliminated immediately, salts will remain in freshwater environments for years or decades [9,17,18]. Moreover, enacting regulations to protect these systems might present significant challenges, because many activities causing freshwater salinization are associated with significant sources of economic and social wellbeing [19].…”
Section: Introductionmentioning
confidence: 99%